A randomized controlled trial comparing treatment with oral agents and basal insulin in elderly patients with type 2 diabetes in long-term care facilities. Issue 1 (28th August 2015) - Pasquel, Francisco J; Powell, Winter; Peng, Limin; Johnson, Theodore M; Sadeghi-Yarandi, Shadi; Newton, Christopher; Smiley, Dawn; Toyoshima, Marcos T; Aram, Pedram; Umpierrez, Guillermo E
Abstract : Background: Managing hyperglycemia and diabetes is challenging in geriatric patients admitted to long-term care (LTC) facilities. Methods: This randomized control trial enrolled patients with type 2 diabetes (T2D) with blood glucose (BG) >180 mg/dL or glycated hemoglobin >7.5% to receive low-dose basal insulin (glargine, starting dose 0.1 U/kg/day) or oral antidiabetic drug (OAD) therapy as per primary care provider discretion for 26 weeks. Both groups received supplemental rapid-acting insulin before meals for BG >200 mg/dL. Primary end point was difference in glycemic control as measured by fasting and mean daily glucose concentration between groups. Results: A total of 150 patients (age: 79±8 years, body mass index: 30.1±6.5 kg/m 2, duration of diabetes mellitus: 8.2±5.1 years, randomization BG: 194±97 mg/dL) were randomized to basal insulin (n=75) and OAD therapy (n=75). There were no differences in the mean fasting BG (131±27 mg/dL vs 123±23 mg/dL, p=0.06) between insulin and OAD groups, but patients treated with insulin had greater mean daily BG (163±39 mg/dL vs 138±27 mg/dL, p<0.001) compared to those treated with OADs. There were no differences in the rate of hypoglycemia (<70 mg/dL) between insulin (27%) and OAD (31%) groups, p=0.58. In addition, there were no differences in the number of hospital complications, emergency room visits, and mortality between treatment groups. Conclusions: The results of this randomized study indicate that elderly patients with T2D in LTC facilities exhibited similar glycemic control, hypoglycemic events and complications when treated with either basal insulin or with oral antidiabetic drugs. Trial registration number: ClinicalTrials.gov Identifier: NCT01131052 .